Technical, information and innovation risks of industry 4.0 in small and medium-sized enterprises – case of Slovakia and Poland - Snieška, Vytautas; Navickas, Valentinas; Havierniková, Katarína; Okręglicka, Małgorzata; Gajda, Waldemar (Journal of Business Economics and Management, 2020)
The implementation of Industry 4.0 concept brings many risks mainly for small and medium-sized enterprises (SMEs). The objective of the study is a diagnosis and comparison of the perception of selected risk issues connected with Industry 4.0 implementation in Slovak and Polish SMEs, which have knowledge or experience with cluster cooperation. This category of SMEs is specific due to the fact, that not all of the SMEs have experience with cluster cooperation or know this form of doing business. For this purpose, the questionnaire survey of 787 respondents was conducted, focused on the risks of Industry 4.0 that are the most important for SMEs included in three categories: technical readiness, risks of innovation and risks of information. The statistical analysis of the survey results with the application of software STATISTICA and Social Science Statistics calculator leads to the conclusion that, except for the kind of risk of “New products and services”, all the observed risks are perceived as higher by Slovak SMEs than by Polish SMEs. The novelty of this research and its contribution to the body of knowledge lies in identification and evaluation of most important risks for specific group of SMEs related to Industry 4.0 implementation compared in two countries. The results of this research provide useful information for the practical fine-tuning of the policy aimed at transfer to Industry 4.0 in specific field – cluster cooperation, depending on the size of the enterprise.